Atomic force and electron microscopy of silicone composites with nanostructured iron - Valiev Hammat; Stepanov Gennady; Bakhtiyarov Anton; Kirichenko Svaytoslav; Kudryavtsev Andrey; Minaev Andrey; Vlasov Aleksandr; Karnet Yuliya; Kornilova Alla; Bazin Andrey (EPJ Web of Conferences)
Novel magnetoactive thin film composites based on silicone elastomer with nano-structured iron fillers have been synthesized. Atomic force microscopy studies have established these composites surface topography unique sensitivity to restructuring induced by the atomic force microscope probe. Application low external magnetic field also resulted in changing the initial composites surface wrinkled structure. Scanning electron microscopy research allowed determine the filler agglomerates average size from about 100 nm to 5 μm and their distributions in the polymer matrix. These composite systems with variable surface properties, possess tunable microstructure morphology as a result of controlling small external influences. Such magnetoactive thin film smart surfaces with dynamic wrinkles can find wide practical applications in tunable optical and electronic devices with responsive microstructures.